2011 International Conference on Cyberworlds 2011
DOI: 10.1109/cw.2011.23
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Force and Vibrotactile Feedback with Direct Stimulation for Texture Recognition

Abstract: In this paper a study is conducted in order to evaluate three different strategies of haptic feedback for texture discrimination in virtual environments. Specifically, both force and vibrotactile feedback have been evaluated, as well as the direct use of the sense of touch, to detect different textures. To this end, a force feedback Phantom device, a custom built vibrotactile dataglove and paper palpable prototypes, which represent an ideal model of tactile feedback, have been compared. These three methods hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Therefore, there is a need to deliver feedback through nonvisual sensory channels (e.g., verbal, vibrotactile, force, or a combination thereof) to provide effective and easily understood communication for motor learning among the VI population ( 24 , 25 ). Notably, previous research has explored the benefits of using real-time vibrotactile feedback to effectively deliver localized tactile cues to learners ( 26 , 27 ) and provide intervention to improve sensorimotor performance ( 28 , 29 ). The use of vibrotactile feedback in combination with other sensory feedback modalities has been proven to enhance motor learning ability, including when learning a new movement or reviewing a previously learned one ( 26 , 30 , 31 ), as well as when learning, guiding, and practicing physical activities ( 29 , 32 , 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a need to deliver feedback through nonvisual sensory channels (e.g., verbal, vibrotactile, force, or a combination thereof) to provide effective and easily understood communication for motor learning among the VI population ( 24 , 25 ). Notably, previous research has explored the benefits of using real-time vibrotactile feedback to effectively deliver localized tactile cues to learners ( 26 , 27 ) and provide intervention to improve sensorimotor performance ( 28 , 29 ). The use of vibrotactile feedback in combination with other sensory feedback modalities has been proven to enhance motor learning ability, including when learning a new movement or reviewing a previously learned one ( 26 , 30 , 31 ), as well as when learning, guiding, and practicing physical activities ( 29 , 32 , 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Reference [94], the authors performed an experiment where users try to identify texture using tactile gloves and a custom-built haptic device. The experiments showed that tactile gloves reasonably recognised the texture.…”
Section: Haptic Actuatorsmentioning
confidence: 99%
“…Practical considerations, such as financial and operational constraints, may sometimes limit the degree to which sensory stimuli can be provided in many VR applications [ 22 ]. While there is some progress in providing haptic cues [ 23 26 ], there still are significant challenges [ 27 ] that can ultimately decrease overall task efficiency when haptic cues are presented [ 28 ]. Other cues, such as vestibular, olfactory, or gustatory cues are even less well developed for mainstream learning applications.…”
Section: Introductionmentioning
confidence: 99%
“…In real life, this information (bolt meets resistance) would be signalled by simultaneous changes in haptic (torque on the tool), auditory (tool sound) and visual cues (rotation stops). The haptic (torque) cue is difficult to realise in VR [ 11 , 12 , 17 , 25 , 28 ] but representing this functional event is relatively easy in VR by providing alternative haptic signals. We adopted a novel approach to provide an additional informational value of sensory cues during the virtual training.…”
Section: Introductionmentioning
confidence: 99%